2019
DOI: 10.1111/jfd.13073
|View full text |Cite
|
Sign up to set email alerts
|

Changes in distribution, morphology and ultrastructure of chloride cell in Atlantic salmon during an AGD infection

Abstract: Amoebic gill disease (AGD) is emerging as one of the most significant health challenges affecting farmed Atlantic salmon in the marine environment. It is caused by the amphizoic amoeba Neoparamoeba perurans, with infestation of gills causing severe hyperplastic lesions, compromising overall gill integrity and function. This study used histology, transmission electron microscopy (TEM), immunohistochemistry and transcript expression to relate AGD‐associated pathological changes to changes in the morphology and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…Gills are also responsible for ion balance and the removal of metabolic wastes from the amino acid catabolism [ 10 ]. Recently, Chang et al [ 11 ] showed that AGD‐associated pathology led to changes in morphology and distribution of chloride cells in the gills of Atlantic salmon. The basal epithelial hyperplasia during progression of an AGD infection coincided with a marked reduction in numbers of Na+/K+‐ATPase positive chloride cells and mRNA expression of the gene encoding for this enzyme [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gills are also responsible for ion balance and the removal of metabolic wastes from the amino acid catabolism [ 10 ]. Recently, Chang et al [ 11 ] showed that AGD‐associated pathology led to changes in morphology and distribution of chloride cells in the gills of Atlantic salmon. The basal epithelial hyperplasia during progression of an AGD infection coincided with a marked reduction in numbers of Na+/K+‐ATPase positive chloride cells and mRNA expression of the gene encoding for this enzyme [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chang et al [ 11 ] showed that AGD‐associated pathology led to changes in morphology and distribution of chloride cells in the gills of Atlantic salmon. The basal epithelial hyperplasia during progression of an AGD infection coincided with a marked reduction in numbers of Na+/K+‐ATPase positive chloride cells and mRNA expression of the gene encoding for this enzyme [ 11 ]. This suggested an impairment of the osmo-regulatory capacity of AGD-affected gills.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the number of chloride cells in AGD lesions suggests that the osmoregulatory capacity of affected fish may be compromised, 168,181,182 reducing their tolerance of high salinities. This could indicate that offshore locations are even more unforgiving for affected fish.…”
Section: Agd and Offshore Farmsmentioning
confidence: 99%
“…The site of amoeba attachment is characterized by epithelial desquamation and edema, epithelial hyperplasia, fusion of secondary lamellae, and interlamellar vesicle formation (5). A reduction in chloride cells is also associated with clinical AGD and is closely linked to epithelial hyperplasia (6). An infiltration of inflammatory immune cells, such as neutrophils and macrophages, can be observed within the central venous sinus adjacent to AGD lesions (5,7).…”
Section: Introductionmentioning
confidence: 99%